Indonesia MICE green building project with value engineering and its influential factors: an SEM-PLS approach - Albert Eddy Husin; Sutikno Sutikno; Ato Muhan Iswidyantara (Universitas Mercu Buana, 2023)
The MICE industry is considered one with high economic attractiveness for investors. Regulations and user requests for a new building are required to meet green building standards. The Green Building Council Indonesia issues Greenship's green building certification system. A minimum of 56 points is required for additional investment costs but will result in savings in operations to get a platinum rating. This paper aims to determine what factors are influential in optimising construction costs through the value engineering method to achieve a green building rating tool with life cycle costs using Structural Equation Modelling. The finding is that energy is the most influential factor in obtaining platinum rating certification, which requires value engineering and lifecycle cost analysis to achieve optimal investment costs with additional costs from 7,494% to 4,689%. The novelty of this research is that the selection of materials/machines and working methods of the green concept that saves energy needs to be carried out from the beginning of the design to achieve a feasible payback period for new investments, which will be the commitment of the owner to build a green MICE.